Arabic Hidden Crisis at West Sumatran Islamic Universities: ‎‎Vulnerable Vitality and Potential Utility for Learning - Dinata, Rahmat Satria; Budiarti, Meliza; Musalwa; Syafril, Syafrimen; Amelia, Vanadya (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
This study investigates the vitality of the Arabic language and the role of Arabic language landscapes in supporting learning at Islamic universities in West Sumatra. Using a mixed-method Exploratory Sequential Design, data were collected through observations, focus group discussions, and surveys. Although Arabic signage is commonly found on campuses, its distribution is uneven and its use inconsistent. According to UNESCO’s criteria, Arabic in this context is classified as “vulnerable.” Nevertheless, Arabic landscapes demonstrate potential as learning resources, educational media, and components of a supportive linguistic environment. Students reported improvements in vocabulary and contextual understanding through exposure to these elements. While often symbolic, Arabic landscapes can provide meaningful educational value if effectively integrated. The study concludes that their strategic use could enhance Arabic language learning in higher education. Further research is recommended to involve broader populations and explore innovative approaches to incorporating Arabic landscapes into both formal and informal learning environments.